Chemical pollutants in the respiratory zone of welders: Determination of concentrations and hazard analysis. - Mehrifar, Younes; Zeverdegani, Sara Karimi; Rismanchian, Masoud (Work, 2020)
BACKGROUND: Welding pollutants have potentially dangerous effects on the health of welders. Analysis of exposure risks is an appropriate method for industrial hygiene occupational exposure. OBJECTIVE: The present study aimed to determine the concentrations of exposure and risk evaluation of welders to fumes and gases in three common types of welding including Shielded Metal Arc Welding (SMAW), Gas Metal Arc Welding (GMAW) and Gas Tungsten Arc Welding (GTAW). METHODS: This cross-sectional study was carried out at a steel company. Samples were taken from manganese, chromium and nickel fumes with NIOSH 7300 method and for NO, NO2, CO and O3 gases using direct reading instruments. SQRCA method was used to assess the level of exposure risk. RESULTS: Our study showed that the highest and lowest concentrations of exposure to gases were observed in MIG and GTAW welding, respectively. Also, the highest and lowest concentrations of exposure to metals were observed in SMAW and GTAW processes, respectively. Mean exposure to M, Cr and Ni metals was 2.302, 3.195, and 1.241 mg/m3, respectively. Also, mean exposure to CO, NO, NO2 and O3 was 43.05, 27.88, 4.30, and 0.41 ppm, respectively. Results of risk analysis showed that O3, NO2 and Cr had high and very high risk levels in all welding processes. CONCLUSIONS: MIG and SMAW welders have a high occupational exposure to metal and toxic gases in welding. Preventive measures such as assessment of workplace air, installation of the ventilation systems, and providing appropriate respiratory protection devices for welders should be taken.